2010
DOI: 10.1002/bjs.6879
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile perfusion preservation of warm ischaemia-damaged experimental kidney grafts

Abstract: This study demonstrated that the function of warm ischaemia-damaged kidney grafts after pulsatile perfusion preservation was comparable to that of non-ischaemic controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…These results are in contrast to studies using nonoxygenated cold perfusion at relatively high pressure (30 mm Hg) in pigs, 30 but in line with other previous studies on low pressure oxygenated and endischemic cold kidney perfusion. 31,32 The beneficial effects of HOPE were completely lost when oxygen in the perfusate was replaced by nitrogen, pointing to the key function of perfusate oxygen. Second, we believe that the success of HOPE in kidneys depends strongly also on low pressure conditions (<20 mm Hg), similar to livers, 8 due to a high risk of shear stress and endothelial damage during cold perfusion of kidneys at a perfusion pressure >20 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to studies using nonoxygenated cold perfusion at relatively high pressure (30 mm Hg) in pigs, 30 but in line with other previous studies on low pressure oxygenated and endischemic cold kidney perfusion. 31,32 The beneficial effects of HOPE were completely lost when oxygen in the perfusate was replaced by nitrogen, pointing to the key function of perfusate oxygen. Second, we believe that the success of HOPE in kidneys depends strongly also on low pressure conditions (<20 mm Hg), similar to livers, 8 due to a high risk of shear stress and endothelial damage during cold perfusion of kidneys at a perfusion pressure >20 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we believe that the success of HOPE in kidneys depends strongly also on low pressure conditions (<20 mm Hg), similar to livers, 8 due to a high risk of shear stress and endothelial damage during cold perfusion of kidneys at a perfusion pressure >20 mm Hg. 8,32 On the basis of these observations, the current clinical practice of DCD kidney perfusion may need to be adapted, being most frequently continuous cold perfusion using a pressure of (30/20 mm Hg) LifePort Kidney Transporter (Organ Recovery Systems, Chicago, IL) without active oxygenation. 4,7,31 Notably, the difference between both perfusion techniques appears multifactorial because of several varying parameters, for example, perfusate composition, temperature, pO 2 , and perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Since Ecosol solution meets these requirements, we postulated that Ecosol could be employed for a comparison of VSOP and OMP as well as for CS. Colloids and impermeants prevent extravasation of the preservation solution during washout and perfusion, and therefore form essential components for MP and OMP [50,51,52,53]. Addition of free radical scavengers to clinically applied preservation solutions has been demonstrated to result in an improved efficacy of VSOP and OMP, in particular for the preservation of DCD kidneys and livers [45,54,55,56,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, potential post-operative beneficial effects of MP preservation were also found for DCD donors [22,23,25] and in experimental animal models of DCD [24]. As found in ECD donors, it was possible to observe improvements in early transplantation outcomes, such as DGF, when comparing MP preservation with CS of kidneys from DCD donors [22,23,25], despite the fact that this type of donor is generally more at risk of developing DGF and other post-transplant complications [25].…”
Section: Clinical and Pre-clinical Studiesmentioning
confidence: 66%
“…Authors additionally found shorter hospitalization times and improved post-operative (7 and 30 days) and early (6 and 12 months) graft function for MP-preserved kidneys compared to CS (p=0.05) [23]. Improved renal function upon MP preservation was also found for an experimental pig model of warm ischemia damaged organ, in which the warm ischemia damaged grafts preserved with MP showed kidney functions comparable to that of the non-ischemic controls [24]. Despite the findings from the studies cited above, a UK multicenter randomized controlled trial [26] showed that MP offered no advantages over CS (in terms of DGF incidence and graft and patient survival), for kidneys from controlled DCD donors, with mean warm and cold ischemic times of around 15 min and 14 h, respectively.…”
Section: Clinical and Pre-clinical Studiesmentioning
confidence: 80%